2020
DOI: 10.1159/000507886
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in Systemic Sclerosis: An Update

Abstract: Background: Systemic sclerosis is an immune-mediated rheumatic disease characterized by vascular abnormalities, tissue fibrosis and autoimmune phenomena. Summary: Renal disease occurring in patients with systemic sclerosis may have a variable clinicopathological picture. The most specific renal condition associated with systemic sclerosis is scleroderma renal crisis, characterized by acute onset of renal failure and severe hypertension. Although the management of scleroderma renal crisis was revolutionized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 96 publications
0
51
0
2
Order By: Relevance
“…Renal diseases in SSc patients may manifest in different clinicopathological settings, and scleroderma renal crisis is the most severe life-threatening complication [ 57 , 58 ]. In a 154 patient retrospective analysis, Trombetta et al found a high ratio of kidney involvement at lower vitamin D levels [ 22 ], and Groseanu et al reported scleroderma renal crisis more frequently in patients with vitamin D deficiency in their cohort with SSc [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal diseases in SSc patients may manifest in different clinicopathological settings, and scleroderma renal crisis is the most severe life-threatening complication [ 57 , 58 ]. In a 154 patient retrospective analysis, Trombetta et al found a high ratio of kidney involvement at lower vitamin D levels [ 22 ], and Groseanu et al reported scleroderma renal crisis more frequently in patients with vitamin D deficiency in their cohort with SSc [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of renal involvement, even though SRC has become quite a rare complication in SSc patients, most of the research is focused on this life-threatening complication [7,40]. The latest research supports a potential role for altered Wnt signaling in SRC pathogenesis and indicates that anti-RNA polymerase III autoantibodies seem to be one of the most promising biomarker of renal involment in SSc [31,32] as well as chemerin, which high level is associated with renal function impairment [13].…”
Section: Discussionmentioning
confidence: 99%
“…While many point toward detrimental MMP functions during inflammation, one study has shown inhibited MMP synthesis can lead to excessive collagen deposition in fibrotic intestinal muscles (Bailey et al, 2012). Kidney involvement is also prevalent in SSc patients, leading to scleroderma renal crisis (SRC), promoted by interstitial fibrosis amongst other risk factors (Steen, 2014;Chrabaszcz et al, 2020). Direct MMP involvement in SSc-associated renal fibrosis has not been identified, but numerous studies imply a detrimental role of MMPs in early stages of kidney diseases with ECM-degradative features in later stages during scarring and fibrosis (Ke et al, 2017;Zakiyanov et al, 2019).…”
Section: Mmps In Other Ssc-associated Organ Systemsmentioning
confidence: 99%